Exploring Hemodynamic Responses Using Mirror Visual Feedback With Electromyogram-Triggered Stimulation and Functional Near-Infrared Spectroscopy - Inagaki, Yuji; Seki, Kazunori; Makino, Hitoshi; Matsuo, Yuichirou; Miyamoto, Tamaki; Ikoma, Katsunori (Frontiers in Human Neuroscience, 2019)
In recent years, mirror visual feedback therapy combined with electrical stimulation (ES) have been proposed for patients with hemiparesis. However, the neurophysiological effect remains unknown. We investigated the effects of mirror visual feedback by itself and along with electromyogram-triggered ES on hemodynamic responses using functional near-infrared spectroscopy. Eighteen healthy subjects participated in this study. We measured changes in brain oxygenation using 48 near-infrared spectroscopy channels. We investigated the effects of three main factors of visual feedback (observation of a mark, right hand, and hand movements via mirror) with or without ES on bilateral precentral gyrus, postcentral gyrus, supplementary motor area, supramarginal gyrus area, and angular gyrus to determine the contribution of each factor. The results showed that the left postcentral gyrus was significantly more activated when performing mirrored tasks (MT) than when performing circle or right-hand tasks. In addition, the right postcentral gyrus and right supplementary motor area in MT were significantly more activated than in MT+ES cases. Our findings suggested that observation of movements through the mirror caused activation of the postcentral gyrus rather than the precentral gyrus, and mirror visual feedback along with electromyogram-triggered ES decreased cortical activation.